2019
DOI: 10.1111/sum.12445
|View full text |Cite
|
Sign up to set email alerts
|

Using webinars to extend the reach of soil learning in New South Wales: A first look

Abstract: Increasingly knowledge is shared using new web-based channels. The use of these channels is relatively new in the realm of soil science. However, they may prove to be very useful for connecting time-poor, geographically dispersed audiences in an efficient and cost-effective way. There has been limited study of this form of knowledge sharing for natural science (let alone soil science). In New South Wales (NSW), Australia, the NSW Department of Primary Industries (NSW DPI) has coordinated the Soil Network of Kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…A variety of soil information management and knowledge sharing mechanisms exist, including training workshops (online or offline), websites, social media, advisory services. In Australia, the New South Wales local government uses webinars to disseminate soil science information to a geographically disperse community of practice (CoP) (Jenkins et al, 2019). Grain advisors, however, were reported to be guiding farmers to historically established "rules of thumb" for calculating nitrogen fertilizer needs, rather than the latest evidence-based science on soil water and nitrogen management (Schwenke et al, 2019).…”
Section: Knowledge Transfermentioning
confidence: 99%
“…A variety of soil information management and knowledge sharing mechanisms exist, including training workshops (online or offline), websites, social media, advisory services. In Australia, the New South Wales local government uses webinars to disseminate soil science information to a geographically disperse community of practice (CoP) (Jenkins et al, 2019). Grain advisors, however, were reported to be guiding farmers to historically established "rules of thumb" for calculating nitrogen fertilizer needs, rather than the latest evidence-based science on soil water and nitrogen management (Schwenke et al, 2019).…”
Section: Knowledge Transfermentioning
confidence: 99%
“…Therefore, it has been typical to extend soil information via advisory service providers who share scientific knowledge with farmers one‐on‐one, with behavioural change facilitated by the building of individual and close relationships. State and local governmental agencies can play critical roles in information transmittal processes (Jenkins, Beange, & Morris, 2019). However, in the current movement of sustainable soil management, advisory services also face special challenges owing to farmers’ desire for high‐resolution soil information and practical step‐by‐step guidelines on a farm level, while sustainability is often achieved by integrating considerations across multiple temporal and spatial scales (Ingram & Mills, 2019).…”
Section: Knowledge Sharing: Advisory Services and Workhopsmentioning
confidence: 99%
“…Web‐based information technology allows the transmittal and sharing of soil knowledge at much lower cost than traditional knowledge sharing approaches. Webinars can be used to extend soil knowledge to government advisory services, private advisors and landholders (Jenkins et al., 2019). Online repositories can store large amounts of soil and landscape information collected from field studies, training sessions and land resource assessments (Imhof, Heemskerk, & Cox, 2019).…”
Section: Knowledge Sharing: Information Technology and Social Mediamentioning
confidence: 99%
“…30,31 These studies found that this may be resolved by incorporating useful infographics and webinars that clearly and artfully capture the essence of the research which can reach a geographically dispersed, timepoor audience. 30,32 This can be realised by incorporating the four components of novelty, informativeness, efficiency and aesthetics 30 thus leading to more views of academic journal article abstracts 32 and engagement with target audiences. 32 This study has added to the literature by further strengthening the evidence of the value in co-designing with stakeholders when developing and building community-based websites.…”
Section: How the Website Components Will Address The Needs Of Stakeholdersmentioning
confidence: 99%
“…30,32 This can be realised by incorporating the four components of novelty, informativeness, efficiency and aesthetics 30 thus leading to more views of academic journal article abstracts 32 and engagement with target audiences. 32 This study has added to the literature by further strengthening the evidence of the value in co-designing with stakeholders when developing and building community-based websites. Collectively, this demonstrates how end users can be engaged in a website development process to ensure their needs are met.…”
Section: How the Website Components Will Address The Needs Of Stakeholdersmentioning
confidence: 99%